Financial Liberalization and Business Cycles: The Experience of Countries in the Baltics and Central Eastern Europe - Lúcio Vinhas de Souza (Deutsche Bundesbank, 2004)
This paper extends the work of Kaminsky and Schmukler (2003) to the Baltic and Central Eastern European future Member States of the European Union, to test if the same short-run increase in cyclical volatility arising from financial integration is observed in this specific sample of ?emerging markets?. This work finds some signs that, contrary to other emerging markets, this does not happen: for the future Member States, financial integration, similarly to the outcome observed in mature market economies, reduces cyclical volatility both in the short and in the long run. Weak indications are found that this may happen partially due to the anchoring of expectations provided by the EU Accession, and to the more robust institutional framework imposed by this process onto the countries in question.
Keywords: F34; F02; F30; F33; F32; F36; G15; P20; 330; Enlargement; European Union; financial liberalization; booms; busts; cycles; Bry-Boschan; volatility; Kapitalmarktliberalisierung; Konjunktur; Börsenkurs; Volatilität; Schätzung; EU-Erweiterung; Nordosteuropa; Ostmitteleuropa